Determinación de microalbuminuria y su efectividad en el diagnostico precoz de insuficiencia renal cronica en adultos mayores de 40 años sector el paraiso cantón Buena Fe primer semestre 2015 - Nicola Nuñez, Viviana Cecibel (2015)
Chronic renal failure (CRF) is a global health problem. At present there are approximately 600 million people affected. International data show an increase in the prevalence and incidence of over 10% in the adult population and 20% in those over 60 years.  The main objective of this research was to determine the effectiveness microalbuminuria and early diagnosis of chronic renal failure in adults over 40 year’s industry paradise canton good faith first quarter 2015. Since the technique actually microalbuminuria is a leading indicator of kidney damage and therefore its use in the early diagnosis is very timely. For tabulation of this research surveys were used with closed questions that provided essential data on the subject of study. This research work was made in adults over 40 years. The population and sample consisted of 60 people who formed the object of study. According microalbuminuria levels in relation to the study carried out patients need to control their levels regularly since this allows a great opportunity to be detected early chronic kidney failure.